PENGEMBANGAN MEDIA PEMBELAJARAN MODUL DIGITAL INTERAKTIF PADA MATA PELAJARAN FIQIH MATERI, ZAKAT, INFAQ, DAN SEDEKAH SISWA KELAS X DI MA MUSLIMAT NU PALANGKA RAYA - Aida Nurul Hikmah; Meliny Meliny; Abdul Azis (CV. ADIBA AISHA AMIRA, 2024)
This study aims to develop interactive digital module-based learning media on Fiqh subjects on zakat, infaq, and sedekah for class X students of MA Muslimat NU Palangka Raya. Using the Research and Development (R&D) method with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model, this study produces learning media that has been validated by material and media experts. The validation results show a significant level of feasibility, with a score of 78% from material experts (